Structural basis and kinetics of inter- and intramolecular disulfide exchange in the redox catalyst DsbD - Rozhkova, Anna (Nature Publishing Group, 2004)
DsbD from Escherichia coli catalyzes the transport of electrons from cytoplasmic thioredoxin to the periplasmic disulfide isomerase DsbC. DsbD contains two periplasmically oriented domains at the N- and C-terminus (nDsbD and cDsbD) that are connected by a central transmembrane (TM) domain. Each domain contains a pair of cysteines that are essential for catalysis. Here, we show that Cys109 and Cys461 form a transient interdomain disulfide bond between nDsbD and cDsbD in the reaction cycle of DsbD. We solved the crystal structure of this catalytic intermediate at 2.85 Å resolution, which revealed large relative domain movements in DsbD as a consequence of a strong overlap between the surface areas of nDsbD that interact with DsbC and cDsbD. In addition, we have measured the kinetics of all functional and nonfunctional disulfide exchange reactions between redox-active, periplasmic proteins and protein domains from the oxidative DsbA/B and the reductive DsbC/D pathway. We show that both pathways are separated by large kinetic barriers for nonfunctional disulfide exchange between components from different pathways.